SAE Technical Paper Series 2008
DOI: 10.4271/2008-01-0818
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Brake Judder Investigations Using a High Speed Dynamometer

Abstract: This paper is concerned with addressing the problems experienced with the thermo-elastic behaviour of the disc -that of optimum heat dissipation, and equally important, even heating of the disc blade. The primary objective is to develop a more temperature-stable brake disc.The work presented approaches the problems of thermal judder through benchmarking the current situation. This is approached by modelling the current brake and its validation by means of vehicle and laboratory testing. The empirical work is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In other words it is generated due to temporary geometrical deviations of a disc as temperature goes higher and will disappear with disappearance of geometrical deviations as the disc cools down. It is caused due to high thermal input to the brake in a short period of time that results in a thermoelastic deformation, and eventually thermoelastic instabilities in the form of hot spots [108].…”
Section: Hot Juddermentioning
confidence: 99%
“…In other words it is generated due to temporary geometrical deviations of a disc as temperature goes higher and will disappear with disappearance of geometrical deviations as the disc cools down. It is caused due to high thermal input to the brake in a short period of time that results in a thermoelastic deformation, and eventually thermoelastic instabilities in the form of hot spots [108].…”
Section: Hot Juddermentioning
confidence: 99%
“…For example, a fully coupled transient thermo-mechanical finite element model of a brake disk and pad assembly involving complex eigenvalue analysis was developed by Hassan et al 14 to evaluate brake squeal. They concluded that the squeal frequency and intensity are dependent on the interface contact conditions, which can be validated by an in-house brake dynamometer designed by Bryant et al 15 The friction torque variation can be employed to reflect hot judder through Park et al 16 and Jung et al, 17 who established three-dimensional finite element models in SAMCEF to investigate the hot judder phenomenon.…”
Section: Introductionmentioning
confidence: 95%
“…Boulahbal [14] presented a unified framework for addressing NVH-related issues attributed to tyre uniformity and brake rotor DTV. Some researchers also investigated the thermal brake judder, analysed the mechanism of hot brake judder, and presented various measures to reduce thermal brake judder [15,16].…”
Section: Introductionmentioning
confidence: 99%